(untitled) (Heritage, 2022)
Language disorder is defined as a disorder of the acquisition, comprehension or expression of spoken and/or written language that may be expressed in one or more aspects of the language system including phonology, semantics, morphology, syntax and pragmatics. Difficulties at the level of morphology and syntax are by far the most recognizable and most researched linguistic aspects, while research on other aspects of language has been left aside. The aim of this study was to determine the distinctive features of the deficit of articulation-phonological and lexical-semantic abilities in children with developmental language disorder (DLD) at a younger school age. Our research included 79 respondents, 39 of them with a diagnosis of DLD and 40 children with typical language development. The average age of the respondents in the group of children with DLD was 6.87 years, while the age of the respondents in the control group was 6.93. In the research, a prepared battery of tests was used to assess articulation-phonological abilities (Global Articulation Test, Oral Praxis Test, Phoneme Difference Test and Auditory Discrimination Test), while Vocabulary and Semantic Test was used to assess lexical and semantic abilities. Children with DLD had higher average scores on all tests used, but discriminant analysis found that synonyms, oral practice, metonyms, phonemic hearing, and auditory discrimination contributed most to group discrimination, while other variables contributed but with less projection. It is important to mention that the articulation slightly contributes to group discrimination.